ЖИСМОНИЙ ТАРБИЯ ЎҚИТУВЧИЛАРИНИНГ КАСБИЙ ФАОЛИЯТГА ТАЙЁРЛАШ параметрлари - Махмудов, Б.А. (FAN va JAMIYAT, 2018)
The article gives a good idea of the improvement of the parameters of the professional activities of future physical education of teachers, which outlines the information that must be made to prepare the teacher of physical education today.